Peningkatan Perkembangan Kognitif Siswa melalui Musik dan Lagu dalam Pembelajaran - Ni Putu Liana Octavyanti; Ni Ketut Suarni; I Gede Margunayasa (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to describe the effect of increasing students' cognitive development through music and songs in learning. Learning at school must be carried out in a way that is fun and creates meaning. One way is to use music and introduce children's songs. Through music and songs in learning, students will be able to develop their cognitive abilities and adapt them to the realities of life. This research uses a literature study method with 4 stages, namely choosing the topic to be studied review, selecting relevant articles, conducting literature analysis and synthesis, and organizing writing review. Data was analyzed from journal findings, scientific articles, literature review which contains the design that will be examined, then compiles the results of the findings that have been carried outreview. The results of this research show that learning using music and songs has an influence on the cognitive development of students in elementary schools which includes: strengthening understanding of concepts, improving student learning outcomes, being able to solve problems, thinking critically, and increasing student creativity. Apart from that, it can also create a feeling of joy, excitement and enthusiasm for learning so that it can create a pleasant learning atmosphere.